Femoral bone metastasis is a poor prognostic factor in EGFR-TKIs-treated patients with -mutated non-small-cell lung cancer: a retrospective, multicenter cohort study - Ichidai Tanaka; Kazumi Hori; Junji Koyama; Soei Gen; Masahiro Morise; Yuta Kodama; Akira Matsui; Ayako Miyazawa; Tetsunari Hase; Yoshitaka Hibino; Toshihiko Yokoyama; Tomoki Kimura; et al. (Therapeutic Advances in Medical Oncology)
Background: Epidermal growth factor receptor ( EGFR )-mutant non-small-cell lung cancers (NSCLCs) have higher frequencies of bone metastases than those of wild type; however, the metastatic pattern and influence on clinical outcome remain unclear. Objectives: To analyze the association between bone metastatic sites and the clinical efficacy of the first-, second-, and third-generation EGFR-tyrosine kinase inhibitors (TKI), in these patients. Design: Retrospective multicenter cohort study. Methods: The clinical data of patients with advanced-NSCLC harboring EGFR mutation, who were treated by EGFR-TKIs as first-line treatment at five medical institutions ( N  = 411), were retrospectively assessed for bone metastatic sites, overall survival (OS), and progression-free survival (PFS). Results: Bone metastases were found in 41.1% of the patients at diagnosis, including 13.1%, 8.0%, and 20.0 for single, double, and multiple lesions (⩾3), respectively. The vertebra (76.3%) and pelvis (60.9%) were the most frequent metastatic sites. Femoral-, sternum-, and scapula-metastases were remarkably increased in the patients with multiple-bone metastases. In the EGFR -mutant NSCLC patient treated with osimertinib, both the OS and the PFS of the patients with femoral bone metastasis were significantly shorter than those of the patients without femoral bone metastasis (OS: not reached vs 12.1 months, p  < 0.0001; and PFS: 17.2 vs 9.3 months, p  < 0.0018). Furthermore, a multivariable Cox regression analysis, including several poor prognostic factors, such as L858R mutation and liver metastasis, demonstrated that femoral bone metastasis was a statistically independent predictor of OS. Conclusion: Femoral bone metastasis is associated with poor survival of EGFR -mutant NSCLC patients who were treated with EGFR-TKIs, including osimertinib, and is an independent prognostic factor of OS.